Rancang Bangun Sistem Inventaris pada UMKM Girimulyo, Kabupaten Lampung Timur - Anggraini, Leslie; Bagaskara, Radhinka; Verdiana, Miranti; Afriansyah, Aidil; Idris, Mohamad (Nemui Nyimah, 2025)
We discuss the design and implementation of an Inventory Management System developed specifically for Javamart Girimulyo to enhance accuracy and efficiency in stock control. The primary objective of the system is to automate inventory tracking, monitor stock levels in real time, and generate detailed inventory reports, thus minimizing manual errors and improving overall inventory oversight. The development followed the Modified Waterfall methodology, which provided a clear and systematic process across stages of requirements gathering, system design, coding, testing, and deployment. Key functionalities include automatic stock updates upon item inflow and outflow, low-stock alerts, flexible item categorization, and secure access controls for administrators. The system also offers an intuitive graphical user interface and integrates with a MySQL database backend to ensure data reliability and consistency. Testing outcomes indicate that the system delivers the necessary performance and stability, confirming its suitability for deployment. By digitizing and streamlining stock management processes, this project offers a practical and scalable solution to support inventory operations at Javamart Girimulyo.